Repair of symptomatic superior mesenteric artery pseudoaneurysm with arteriovenous fistula using physician-modified endograft - Olivia Fuson, MD; Claire Janssen, MD; Andrew Barleben, MD; Ann Gaffey, MD, MS (Journal of Vascular Surgery Cases and Innovative Techniques)
Superior mesenteric artery (SMA) pseudoaneurysm with superior mesenteric arteriovenous fistula (SMAVF) is a rare pathology associated with high rates of rupture and mortality. Known interventions for the treatment of SMA pseudoaneurysm with SMAVF include open repair or endovascular repair with coil embolization or covered stenting. To the best of our knowledge, this report is the first of physician-modified endograft for the treatment of SMA pseudoaneurysm with SMAVF after prior thrombosis, ligation, and coil embolization of the SMA. The patient recovered well and has 1 month of follow-up after the procedure.